2012
DOI: 10.1089/neu.2012.2373
|View full text |Cite
|
Sign up to set email alerts
|

Motor Vehicle Crash-Related Subdural Hematoma from Real-World Head Impact Data

Abstract: Approximately 1,700,000 people sustain a traumatic brain injury (TBI) each year and motor vehicle crashes (MVCs) are a leading cause of hospitalization from TBI. Acute subdural hematoma (SDH) is a common intracranial injury that occurs in MVCs associated with high mortality and morbidity rates. In this study, SDH volume and midline shift have been analyzed in order to better understand occupant injury by correlating them to crash and occupant parameters. Fifty-seven head computed tomography (CT) scans were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Models should be validated against additional displacement tests (Hardy et al 2001, Hardy 2007) in the future as well as against strain data from live humans obtained by magnetic resonance elastography (MRE) studies (Sabet et al 2008). Injury prediction capabilities will continue to increase as brain models are improved and validated against more experimental data and further correlated with real world injuries (Urban et al 2012, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Models should be validated against additional displacement tests (Hardy et al 2001, Hardy 2007) in the future as well as against strain data from live humans obtained by magnetic resonance elastography (MRE) studies (Sabet et al 2008). Injury prediction capabilities will continue to increase as brain models are improved and validated against more experimental data and further correlated with real world injuries (Urban et al 2012, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Cortical thickening during initial scans following an mTBI and cortical thinning in later scans may reflect progressive normalization of CT, that is, physical recovery from brain lesions (Lewen et al, ; Wang et al, ). In addition, the brain areas, such as RMFG, which are more susceptible to direct impacts following a frontal–rear axis head injury, may result in the release of excitotoxins from damaged tissues causing inflammatory reactions, including microedema (Barkhoudarian, Hovda, & Giza, ; Lillie, Urban, Lynch, Whitlow, & Stitzel, ; Patterson and Holahan, ; Urban et al, ). These inflammatory reactions have been reported to elevate fractional anisotropy, thicken the cortical regions initially but cause cortical thinning over time with the reduction of microedema (Lewen et al, ; Ling et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…21 In the current study, we identified cortical thickening in rMFG and precuneus areas that are vulnerable to direct impacts from coup/contrecoup injury in frontalrear axis head injury. 31,55 If the mTBI caused a local release of excitotoxins from damaged cells in these regions, 56 these in turn can contribute to inflammatory reactions, possibly including micro-edema. [57][58][59] Consistent with this possibility, a recent study reported elevated cortical fractional anisotropy in similar regions, 14 days to 4 months after mTBI, which could also be the consequence of cytotoxic edema.…”
Section: Figmentioning
confidence: 99%